Portals and doors in traditional Ohrid architecture - Nikoljski Panevski Elena; Karanakov, Vladimir (Ss. Cyril and Methodius University in Skopje, Faculty of Design and Technologies of Furniture and Interior in Skopje, 2013)
The basis for this scientific work is traditional Macedonian architecture, with emphasis on old doorway of family houses and religious objects (sacral and profane architecture). Ohrid has always been interesting for examination from these aspects, because of the fact that it has lots of historical monuments. The old part of the city contains houses, museums and churches which are one of the quality examples for traditional Macedonian architecture. The main purpose of this paper is to learn more about details in architecture, and of course, the value of details, especially old doors, portals, their dimensions, characteristics, art style, their constructors etc. This is because there is a lot of information originating from literature, books, study works and other written sources about Macedonian traditional architecture, but there is not much information about their details such as doors, windows, portals, etc. These beautiful, genius objects were built in the 19 th century. Today, they attract people who love art with its special charm and beauty, and inspire specialists - architects - for its contemporary application and creation, releasing it from fake values. There are many towns in Macedonia with well-preserved architecture dating from the 19th century: Krushevo, Kratovo, Novo Selo, Tetovo, Debar, Struga, Prilep, Kriva Palanka, Strumica. Central place among them takes Ohrid, in particular ancient Lychinidos.
Keywords: details in traditional Macedonian architecture; portal; doors; gateway; meaning and value of traditional houses; examination methods; construction skill; national constructor; anthropomorphic measurements and decoration